2010
DOI: 10.1128/jvi.02614-09
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Phenotypic Characterization of GII-4 Noroviruses That Circulated during 1987 to 2008

Abstract: The predominance and continual emergence of new variants in GII-4 noroviruses (NVs) in recent years have raised questions about the role of host immunity and histo-blood group antigens (HBGAs) in NV evolution. To address these questions, we performed a genetic and phenotypic characterization of GII-4 variants circulating in the past decade (1998 to 2008). Ninety-three GII-4 sequences were analyzed, and of them, 16 strains representing 6 genetic clusters were selected for further characterization. The HBGA bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 76 publications
(135 reference statements)
3
68
1
1
Order By: Relevance
“…GII. bound to H type 3, Lewis Y, and B trimer (29,48). Consistent with our previous report (29), a ligand binding partner for GII.4-2004 VLP was not identified in this assay, perhaps reflecting residue microvariation occurring within the different GII.…”
Section: Anti-gii4-2002 Mab Reactivitysupporting
confidence: 78%
See 2 more Smart Citations
“…GII. bound to H type 3, Lewis Y, and B trimer (29,48). Consistent with our previous report (29), a ligand binding partner for GII.4-2004 VLP was not identified in this assay, perhaps reflecting residue microvariation occurring within the different GII.…”
Section: Anti-gii4-2002 Mab Reactivitysupporting
confidence: 78%
“…These data suggest that these antibodies (anti-GII.4-2002-G1, -G2, -G3, and -G4) do not recognize neutralizing epitopes, and although not informative about viral antigenic evolution, they do provide potential diagnostic reagents for detection of broader groups of NoV strains. These antibody reactivity patterns are reminiscent of those generated by immunizing mice with P particles (48), as the antibodies react with denatured capsid protein by Western blot analysis but did not block VLP-ligand interactions. These data underscore an important complication of using Western blot analysis to determine the antigenic relatedness of GII.4 strains.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, some of these changes are in close proximity to HBGA binding sites, particularly site 2, and thus could potentially affect HBGA binding in the 2004 variant. Regarding HBGA binding in the 2004 variants, there have been conflicting reports (9,10,43). To examine if the changes observed for the 2004 P domain structure influence the HBGA binding preference of the 2004 variant, we carried out cocrystallization experiments with both monofucosyl ABH HBGAs and difucosyl secretor Lewis HBGA, for which the structure in complex with GII.4 has not been previously reported.…”
Section: Resultsmentioning
confidence: 99%
“…4 2004-2005 variants showed that these variants do not bind to any known carbohydrates, and these variants were suggested to have acquired novel receptors or novel carbohydrate ligands (10). Another study using recombinant P particles, higher-order oligomers of the P domain obtained by using a cysteine-linked peptide at one of the termini, indicated that these variants bind to all of the secretor HBGAs although to a lesser extent than those of other variants (43). Finally, most recently, de Rougemont et al, using a variety of binding studies, including surface plasmon resonance with well-characterized VLP preparations, have shown that the 2004-2005 variants bind to both ABH and Lewis secretor HBGAs (9).…”
mentioning
confidence: 99%